Disk Instability Model for Quasi-periodic Eruptions: Investigating Period Dispersion and Peak Temperature - Pan, Xin; Li, Shuang-Liang; Cao, Xinwu; Liu, Bifang; Yuan, Weimin (The Astrophysical journal, 2025)
Quasi-periodic eruptions (QPEs) are a class of X-ray repeating burst phenomena discovered in recent years. Although many models have been proposed to study this phenomenon, there remains significant debate regarding the physical origin of QPEs. In our previous work, we developed a disk instability model with a large-scale magnetic field and successfully reproduced the light curves and spectral characteristics of several QPE sources. We further investigate this model in this work, aiming to explain two key observational features: the dispersion in eruption periods and the peak temperatures during eruptions. This model reveals critical thresholds ( M ̇ crit , β 1,crit ) that separate systems into stable regimes with minimal period variations and unstable regimes where periods are highly sensitive to the accretion rate and magnetic field parameter, while peak temperatures remain nearly constant across the parameter space. This framework successfully explains both the regular eruptions observed in sources such as GSN 069 and the stochastic behavior in sources such eRO-QPE1, while simultaneously accounting for the observed temperature stability during long-term evolution of QPEs.